Private Pensions Market Development in Romania in 2014 - Tudor Colomeischi; Eugenia Iancu (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
The main directions on which channeled the FSA (Financial Surveillance Authority) the activity in Romania in 2014 were the development of non-bank financial markets and their contribution to economic growth. In this article we propose an analysis of how it has evolved the private pensions market in Romania in 2014. We took into account the dynamics of assets, investments and the average rate of return of private pension funds
Keywords: E2; E6; 330; private pensions; active; investments; market; bonds; government securities